2002
DOI: 10.4049/jimmunol.169.10.6005
|View full text |Cite
|
Sign up to set email alerts
|

The T Cell Response to Art v 1, the Major Mugwort Pollen Allergen, Is Dominated by One Epitope

Abstract: Mugwort (Artemisia vulgaris) pollen allergens represent the main cause of pollinosis in late summer in Europe. At least 95% of sera from mugwort pollen-allergic patients contain IgE against a highly glycosylated 24- to 28-kDa glycoprotein. Recently, this major allergen, termed Art v 1, was characterized, cloned in Escherichia coli, and produced in recombinant form. In the present study we characterized and compared the T cell responses to natural (nArt v 1) and recombinant Art v 1 (rArt v 1). In vitro T cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 29 publications
1
104
0
Order By: Relevance
“…Another study in humans has reported the existence of Th2-type CD4 ϩ T cells directed against a single immunodominant epitope from mugwort pollen in allergic patients, which coexisted with Ag-specific IgE Abs and exhibited a large TCR repertoire (52). These observations led us to examine the TCR repertoire of the TRAG-3-specific CD4 ϩ T cells derived from PBL of either a melanoma patient with TRAG-3-expressing tumor or a normal donor.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in humans has reported the existence of Th2-type CD4 ϩ T cells directed against a single immunodominant epitope from mugwort pollen in allergic patients, which coexisted with Ag-specific IgE Abs and exhibited a large TCR repertoire (52). These observations led us to examine the TCR repertoire of the TRAG-3-specific CD4 ϩ T cells derived from PBL of either a melanoma patient with TRAG-3-expressing tumor or a normal donor.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of serum IgE to ragweed and mugwort pollen extracts was tested in immunoblots as described previously (20). Allergen-specific ELISAs were performed as described previously (21) using nAmb a 1 and nArt v 6, respectively.…”
Section: Allergen-specific Ige Bindingmentioning
confidence: 99%
“…PBMCs (2 3 10 5 ) were stimulated in triplicates with concentrations from 0.3 to 20 mg/ml rAmb a 1 or rArt v 6. Allergen-specific TCL were established as described previously (20). In brief, 1.5 3 10 6 PBMCs were initially stimulated either with ragweed or mugwort pollen extract (10 mg/ml), Amb a 1 (2.5 mg/ml), or Art v 6 (2.5 mg/ml).…”
Section: Allergen-specific T Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations